Commercial banks regulation and intermediation function in an emerging market - Amalachukwu Chijindu Ananwude; Steve Nkem Ibenta; Gideon Kasie Ezu; Celestine Sunday Okaro (Economic Journal of Emerging Markets, 2021)
Purpose - This paper investigates the effect of commercial bank regulations, namely the price, product, and geographic regulations, on the intermediation function of commercial banks in Nigeria. Methods - Using secondary data from 1986 to 2017 from the Central Bank of Nigeria (CBN) and the World Bank, this study employs the Autoregressive Distributive Lag (ARDL) model and Granger causality framework.Findings - This paper provides evidence of a long-run relationship between commercial bank regulation and intermediation function represented by private sector credit to RGDP (regional gross domestic product). It also finds that commercial banks' regulation index through price, product, and geographic regulation has a positive relationship with intermediation function. Furthermore, the long-run relationship between commercial bank regulation and intermediation function described by private sector credit to RGDP is affirmed.Implication - The Central Bank of Nigeria (CBN) needs to relax the product regulation to allow commercial banks to engage in various conventionally non-banking activities.Originality - The paper contributes to the literature by ascertaining the commercial banks' intermediation function to Nigeria's economic growth and development.